New benchmarks to design clinical trials with advanced or metastatic liposarcoma or synovial sarcoma patients: an EORTC - Soft Tissue and Bone Sarcoma Group (STBSG) meta-analysis based on a literature review for soft-tissue sarcomas - Kantidakis, Georgios; Litière, Saskia; Neven, Anouk; Vinches, Marie; Judson, Ian; Blay, Jean-Yves; Wardelmann, Eva; Stacchiotti, Silvia; D'Ambrosio, Lorenzo; Marréaud, Sandrine; van der Graaf, Winette T. A.; Kasper, Bernd; et al. (European journal of cancer, 2022)
Background - Recently, we performed a meta-analysis based on a literature review for STS trials (published 2003-2018, ≥10 adult patients) to update long-standing reference values for leiomyosarcomas. This work is extended for liposarcomas (LPS) and synovial sarcomas (SS). - Materials and methods - Study endpoints were progression-free survival rates (PFSRs) at 3 and 6 months. Trial-specific estimates were pooled per treatment line (first-line or pre-treated) with random effects meta-analyses. The choice of the therapeutic benefit to target in future trials was guided by the European Society for Medical Oncology Magnitude of Clinical Benefit Scale (ESMO-MCBS). - Results - Information was acquired for 1030 LPS patients (25 trials; 7 first-line, 17 pre-treated, 1 both) and 348 SS patients (13 trials; 3 first-line, 10 pre-treated). For LPS, the overall pooled first-line PFSRs were 69% (95%-CI 60-77%) and 56% (95%-CI 45-67%) at 3 and 6 months, respectively. These rates were 49% (95%-CI 40-57%)/28% (95%-CI 22-34%) for >1 lines. For SS, first-line PFSRs were 74% (95%-CI 58-86%)/56% (95%-CI 31-78%) at 3 and 6 months, and pre-treated rates were 45% (95%-CI 34-57%)/25% (95%-CI 16-36%). Following ESMO-MCBS guidelines, the minimum values to target are 79% and 69% for first-line LPS (82% and 69% for SS) at 3 and 6 months. For pre-treated LPS, recommended PFSRs at 3 and 6 months suggesting drug activity are 63% and 44% (60% and 41% for SS). - Conclusions - New benchmarks are proposed for advanced/metastatic LPS or SS to design future histology-specific phase II trials. More data are needed to provide definitive thresholds for the different LPS subtypes.
Online verfügbar: 8 September 2022, Artikelversion: 15 September 2022
Gesehen am 14.08.2023